2009
DOI: 10.1556/aagr.57.2009.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Spot blotch and terminal heat stress tolerance in south Asian spring wheat genotypes

Abstract: Terminal heat stress and spot blotch disease (caused by Cochliobolus sativus) are the most important stresses responsible for significant yield losses every year in warm South Asian plains. Both of these stresses are very severe in late planted wheat, which is common in rice-wheat and rice-rice-wheat cropping systems. The development of genotypes tolerant to both stresses might be very useful for increasing yield and reducing yield losses. Information is limited on how different genotypes respond to both stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
3
5
0
Order By: Relevance
“…On the other hand, BL1473, a highly susceptible genotype, showed tolerance to both spot blotch and heat stress (Table 3). The result is consistent with previous reports (Rosyara et al 2005(Rosyara et al , 2007(Rosyara et al , 2009b. BL1473 also showed higher compensation to removal of the flag and penultimate leaves (Rosyara et al 2005) indicating some type of compensation mechanism.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, BL1473, a highly susceptible genotype, showed tolerance to both spot blotch and heat stress (Table 3). The result is consistent with previous reports (Rosyara et al 2005(Rosyara et al , 2007(Rosyara et al , 2009b. BL1473 also showed higher compensation to removal of the flag and penultimate leaves (Rosyara et al 2005) indicating some type of compensation mechanism.…”
Section: Discussionsupporting
confidence: 93%
“…In the present work, water withholding at first node appearance resulted in higher grain mass per plant, but there was a decline in the thousand-kernel mass. In response to abiotic and biotic stress, Rosyara et al (2009) reported reductions in both the yield and the thousand-kernel mass, but observed no changes in other yield parameters. By contrast, in the present work water withholding in the early stage of development resulted in a decrease in the grain number.…”
Section: Discussionmentioning
confidence: 94%
“…Attributing to the fact that south Asian wheat growing season is characterised by high humidity and high temperature, it is favourable for spot blotch particularly during flowering and grain filling stage 2 , 18 . Heat stress and spot blotch have been found to be positively associated 19 . Moderate to warm temperature range (18 to 32 °C) generally favours the growth of spot blotch pathogen Bipolaris sorokiniana .…”
Section: Introductionmentioning
confidence: 97%
“…Most of earlier studies have focused on separate investigations of spot blotch or terminal heat stress in wheat, often in T. aestivum × T. aestivum crosses. Although a few studies have attempted to investigate the effects of the simultaneous stresses 11 , 19 , they do not provide comprehensive insights under controlled individual and combined stress conditions.…”
Section: Introductionmentioning
confidence: 99%